2013
DOI: 10.1126/science.1229573
|View full text |Cite
|
Sign up to set email alerts
|

The Cross-Bridge Spring: Can Cool Muscles Store Elastic Energy?

Abstract: Muscles not only generate force. They may act as springs, providing energy storage to drive locomotion. Although extensible myofilaments are implicated as sites of energy storage, we show that intramuscular temperature gradients may enable molecular motors (cross-bridges) to store elastic strain energy. Using time-resolved small-angle X-ray diffraction paired with in situ measurements of mechanical energy exchange in flight muscle of Manduca sexta we produced high-speed movies of X-ray equatorial reflections i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 30 publications
0
49
0
Order By: Relevance
“…They suggested that the storage and recovery of elastic energy in bound cross-bridges could assist with some of the inertial work of decelerating and accelerating the wings. In this system, the cool temperatures maintained in a portion of the muscle may be critical for allowing cross-bridges to remain bound for long enough to contribute elastically to a portion of the locomotor cycle, as the mechanism does not occur in warmer muscle (George et al, 2013). This study demonstrates that while cross-bridges may be very limited in their overall strain and energy contribution, under just the right circumstances (e.g.…”
Section: Evidence For Energy Storage and Recovery In Muscle Springsmentioning
confidence: 85%
See 1 more Smart Citation
“…They suggested that the storage and recovery of elastic energy in bound cross-bridges could assist with some of the inertial work of decelerating and accelerating the wings. In this system, the cool temperatures maintained in a portion of the muscle may be critical for allowing cross-bridges to remain bound for long enough to contribute elastically to a portion of the locomotor cycle, as the mechanism does not occur in warmer muscle (George et al, 2013). This study demonstrates that while cross-bridges may be very limited in their overall strain and energy contribution, under just the right circumstances (e.g.…”
Section: Evidence For Energy Storage and Recovery In Muscle Springsmentioning
confidence: 85%
“…George and co-workers used X-ray diffraction measurements to show that in hawkmoth muscles, cross-bridges may remain bound as the muscle transitions from lengthening to shortening at the limits of the wingbeat (George et al, 2013). They suggested that the storage and recovery of elastic energy in bound cross-bridges could assist with some of the inertial work of decelerating and accelerating the wings.…”
Section: Evidence For Energy Storage and Recovery In Muscle Springsmentioning
confidence: 99%
“…The antagonistic extension of elastic elements in both passive and active muscle as well as exoskeletal deformations may store and return elastic energy ( Fig. 1 b) [10,11,12,13]. In particular, temperature gradients in Manduca sexta enables crossbridges to remain bound and function as springs, although the energy exchange capacity has not been quantified [13].…”
Section: Introductionmentioning
confidence: 99%
“…Linear and rotary motors are the basic components in mechanical machineries that are crucial to industrialized societies. On the molecular scale, many cell functions in living organisms are driven by similar biological motors, from cargo transportation, gene regulation to muscle contractions . Synthetic motors that can reliably work on the nano‐ and micrometer scales have been pursued by researchers, for their great potential in biomedicine, material science and nanotechnology.…”
Section: Manipulation Of Plasmonic Particles With Optical Forcesmentioning
confidence: 99%